(The effect of an educational curriculum with aids in teaching and development Technical performance of direct free kick and some variables Biomechanical age (15 years old) (International Journal of Psychosocial Rehabilitation, 2020)
The educational curriculum that includes exercises for aids means a great importance in the numbers of the player physically and skillfully, especially beginners, with its characteristics to prepare the athletes as the importance of special exercises lies in the participation of the largest possible number of muscles while improving skills and gaining the linkage of movement parts and that the most important benefit of exercises for aids. It can expand the perception of the player, especially if those exercises for the auxiliary means are prepared players according to the biomechanical variables that contribute to the success of the technical performance in a large way, as organizing the exercises, using scientific methods and investing educational methods based on the correct foundations is the scientific approach that is intended to raise the educational level And achieve the goals of the educational process.